Umbilical cord arterial blood gas analysis in term singleton pregnancies: a retrospective analysis over 11 years - Ji Hee Lee; Jihee Jung; Hyea Park; Seo-yeon Kim; Do youn Kwon; Suk-Joo Choi; Soo-young Oh; Cheong-Rae Roh (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveGiven that the large volume of data on cord arterial blood gas analysis (ABGA) have been rarely addressed in Korean population, we aimed to examine the incidence, associated factors, and neonatal outcomes in cases of low cord pH, and investigate the incidence of cerebral palsy (CP).MethodsFrom data of all consecutive term singleton pregnancies delivered in our institution from 2006 to 2016 (n=15,701), cases with cord ABGA (n=14,221) available were included. We collected information on maternal clinical characteristics and delivery outcomes and also examined neonatal and infant outcomes, including neonatal intensive care unit (NICU) admission and CP, in cases with low cord pH, defined as a pH <7.1.ResultsRates of low Apgar scores at 1 minute (<4) and 5 minutes (<7) were 0.6% (n=79) and 0.4% (n=58), respectively. Rates of cord pH <7.2, <7.1, and <7.0 were 7.1% (n=1,011), 1.1% (n=163), and 0.3% (n=38), respectively. Among cases with low cord pH, 30.1% (n=49/163) were admitted to the NICU and 11.0% (n=18/163) required ventilator support. Ultrasonography of the brain was performed in 28.8% (n=47/163), with abnormal findings observed in 27.7% (n=13/47). Among cases with low cord pH, 1.8% (n=3/163) were subsequently diagnosed with CP, including 2 cases of spastic CP and 1 of ataxic CP.ConclusionAlthough low cord pH was a relatively frequent finding observed in 1 out of every 87 cases, hypoxic-ischemic encephalopathy-related CP was found in only 1 out of 7,111 term singleton deliveries over 11 years in our institution.